1997
DOI: 10.1097/00000539-199701000-00029
|View full text |Cite
|
Sign up to set email alerts
|

Nephrotoxicity of Sevoflurane Versus Desflurane Anesthesia in Volunteers

Abstract: Present package labeling for sevoflurane recommends the use of fresh gas flow rates of 2 L/min or more when delivering anesthesia with sevoflurane. This recommendation resulted from a concern about the potential nephrotoxicity of a degradation product of sevoflurane, "Compound A," produced by the action of carbon dioxide absorbents on sevoflurane. To assess the adequacy of this recommendation, we compared the nephrotoxicity of 8 h of 1.25 minimum alveolar anesthetic concentration (MAC) sevoflurane (n = 10) ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
32
0
2

Year Published

1998
1998
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(34 citation statements)
references
References 30 publications
0
32
0
2
Order By: Relevance
“…So, it seems to have no nefrotoxic effects in men 19 . Some authors have recently observed that sevoflurane in low fresh gases flow may determine renal changes, characterized by increased albumin and glucose urinary excretion, as well as of some tubular enzymes 20,21 . These results, however, have been questioned by other authors 14,22,23 for believing that the best renal changes markers are still plasma urea and creatinine levels, and for the inexistence of significant evidences to credit tubular enzyme changes as major indicators of sevoflurane-induced renal injury.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…So, it seems to have no nefrotoxic effects in men 19 . Some authors have recently observed that sevoflurane in low fresh gases flow may determine renal changes, characterized by increased albumin and glucose urinary excretion, as well as of some tubular enzymes 20,21 . These results, however, have been questioned by other authors 14,22,23 for believing that the best renal changes markers are still plasma urea and creatinine levels, and for the inexistence of significant evidences to credit tubular enzyme changes as major indicators of sevoflurane-induced renal injury.…”
Section: Introductionmentioning
confidence: 99%
“…Mais recentemente, alguns autores verificaram que o sevoflurano, quando empregado em baixo fluxo de gases frescos, pode determinar alterações renais, caracterizadas por aumento da excreção urinária de albumina e glicose, e de algumas enzimas tubulares 20,21 . No entanto, esses resultados têm sido questionados por outros autores 14,22,23 por acreditarem que os melhores marcadores de alterações renais ainda continuam a ser os níveis plasmáticos de uréia e creatinina e por não existirem evidências significativas para se creditarem às alterações enzimáticas tubulares uma indicação importante de ocorrência de lesão renal com o sevoflurano.…”
unclassified
“…However, attempts by other authors to copy the results of these studies failed. Frink et al [27] while using the same experimental protocol and the same laboratory tests were unable to duplicate the type of injury reported by Eger et al [28,29] There is no good explanation for the puzzling results obtained in one single lab. It must not be forgotten that even prolonged (610 h) sevoflurane (high or low fresh gas flow) or isoflurane anaesthesia increased urinary excre- tion of glucose, albumin, protein, and N-acetyl-ß-D-glucosaminidase to the same extent.…”
Section: Human Studiesmentioning
confidence: 92%
“…They reported post-anaesthetic albuminuria indicating injury of the glomerulus, glucosuria and increased urinary ·-GST as signs of proximal tubular injury, and increased urinary -GST indicating distal tubular injury. However, serum routine parameters of renal function such as creatinine, blood urea nitrogen or the ability to concentrate urine (vasopressin test) remained unchanged [28].…”
Section: Human Studiesmentioning
confidence: 99%
“…A number of different groups have been able to identify specific damage to the proximal or distal tubules in the kidney by monitoring urinary GST. One study looked at kidney damage resulting from the administration of the anaesthetic sevoflurane [7]. The authors were able to distinguish between proximal and distal tubular damage by the simultaneous analysis of urinary h and yGST.…”
Section: Introductionmentioning
confidence: 99%